Critical macro-finance: A theoretical lens - Daniela Gabor (Finance and Society, 2020)
This forum contribution outlines four propositions of the critical macro-finance approach: (1) US-led financial globalization has structurally evolved around market-based finance, driven by the production of new asset classes and the Americanization of national financial systems with changing practices for producing liquidity; (2) global finance is a set of interconnected, hierarchical balance sheets, increasingly subject to time-critical liquidity; (3) credit creation in market-based finance involves new forms of money (systemic liabilities); and (4) market-based finance structurally requires a derisking state, for both systemic liabilities and for new asset classes. The precise contours of the derisking state are determined through political struggles.
Keywords: 300